Bridging the gap: Exploring self-regulated learning and academic achievement in Moroccan higher education - Baissane, Omar; Zaid, Hassan (Journal of Interdisciplinary Studies in Education, 2025)
Self-regulated learning (SRL) has been consistently correlated with academic achievement across various educational contexts. Although its importance is widely acknowledged, there remains a notable gap in research on SRL and its predictive power concerning academic achievement within the Moroccan educational setting. This study investigates the relationship between SRL and academic achievement among Moroccan English as a Foreign Language (EFL) university students through a quantitative approach. A total of 403 students completed the Motivated Strategies for Learning Questionnaire, and the data were analyzed via multiple regression analysis. The results revealed a positive relationship, with SRL constructs emerging as significant predictors of academic achievement. The regression model explained 18% of the variance in academic achievement, indicating a moderate but noteworthy impact. The study further discusses practical strategies that educators can adopt to promote SRL, enhance autonomous learning, and equip students with the necessary skills for the complexities of the modern world.